Advanced thin‐film chip concepts for efficient InGaN solar cells. Issue 9 (8th May 2015) - Koch, Holger; Niebling, Tobias; Pietzonka, Ines; Scholz, Dominik; Kalisch, Holger; Vescan, Andrei; Lugauer, Hans‐Jürgen
Abstract: Two chip concepts based on thin‐film technology are presented and compared regarding their suitability for concentrating photovoltaic applications. The main difference is given by the n‐contact design: the first concept relies on a metal grid (MG) while the second one is based on vias (V) connected from the bottom of the solar cell. Although the MG‐chip demonstrated a better performance at low solar concentrations, the V‐chip was found to be more efficient at high concentrations being the relevant operation range for InGaN‐based solar cell applications. Detailed investigations of J – V characteristics applying varied light concentrations revealed a significantly lower series resistance as the main advantage of the V‐concept leading to considerably better fill factors at high solar concentrations.